(untitled) (Heritage, 2024)
The aim of this research was to enhance the understanding of the complex dynamics of poverty and the role of the social welfare system in reducing it by examining the attitudes, experiences, and professional practices of social workers employed in Centers for Social Welfare (CSWs) in the Republic of Serbia (RS). By analyzing legislation and practices related to determining the amount of financial social assistance (FSA), one-time financial aid (OTFA), and lost earnings for working-age household members, the authors identified potential challenges within the support system for the most vulnerable members of society. The sample consisted of 21 professional workers in 12 CSWs in RS. The research was conducted from June 2023 to September 2023. Data were collected through a specially designed questionnaire for this research. The research results indicate low effectiveness of material support in RS, uneven amounts of OTFA, and a lack of consistency in professional procedures across different municipalities in RS.